3D seismic imaging of the Nesjavellir geothermal field, SW-Iceland - Amoroso, Ortensia; Napolitano, Ferdinando; Hersir, Gylfi Pall; Agustsdottir, Thorbjorg; Convertito, Vincenzo; De Matteis, Raffaella; Gunnarsdóttir, Sveinborg Hlíf; Hjörleifsdóttir, Vala; Capuano, Paolo (Frontiers in Earth Science, 2022)
We present a detailed seismic imaging of the harnessed Nesjavellir geothermal area, SW-Iceland, which is one of several geothermal fields on the flanks of the Hengill volcano. We map the vP, vS, and vPvS ratio using seismic data recorded in 2016–2020 and compare them with both a resistivity model of the same area and the rock temperature as measured in boreholes. The results show that the shallower crust (depth less than 1 km) is characterized by low vP and vS, and high vPvS ratio (around 1.9). Shallow low resistivity values at similar depths in the same area have been interpreted as the smectite clay cap of the system. At depths between 1 and 3 km the observed low vPvS ratio of 1.64–1.70 correlates with high resistivity values. In this area, characterized by temperatures larger than 240°C, the seismicity appears to be sparse and located close to the production wells. This seismicity has been interpreted as induced by the production in combination with naturally occurring earthquakes. At depths greater than 4 km, high vPvS ratio of 1.9 correlates well with low resistivity values. In the valley of Nesjavellir, a deep-seated conductive body, domes up at about 4.500 m b.sl. and coincides spatially with a significant high vPvS ratio anomaly (>1.9). Above these anomalies an elevated temperature is registered according to borehole temperature data. This is proposed here to be caused by hot 600°C–900°C cooling intrusives, close to the brittle ductile transition—probably the heat source(s) of the geothermal field above. These anomalies are at the same location as the last fissure eruption in Hengill almost 2,000 years ago. The NNE-SSW trending, deeper seismic cluster at 3–6 km depth is located at the edge of this high vPvS anomaly. The heat source of the Nesjavellir geothermal field is most likely connected to this most recent volcanism as reflected by the deep-seated low resistivity body and high vPvS ratio, located beneath the deep fault that connects the flow path of the high temperature geothermal fluid, resulting in an actively producing reservoir.